Risks and Vulnerabilities along the Life Cycle : Role for Social Protection in Myanmar - Dutta, Puja Vasudeva (World Bank, Washington, DC, 2015)
Myanmar is a country in transition with great regional diversity. It is still a relatively young country with the highest share of its population at active working age. Myanmar’s more pressing needs are the following: a) reducing the incidence of poverty and improving human development outcomes, with a particular emphasis on reaching the poor and vulnerable. Children from poor families fare worse when it comes to nutrition, and education outcomes; and b) addressing the insecurity of incomes and developing mechanisms to reduce exposure to risks and ability to cope with ill-health, disasters and other shocks. This suggests a critical role for social protectionpolicies and programs in Myanmar’s strategy for poverty reduction and people-centered development.